Optimization of Soybean (Glycine max (L.) Merril) Growth and Yield Through the Application of Decanter Solid and Banana Peel Liquid Organic Fertilizer - Wina Apriyani Rajagukgguk; Made Deviani Duaja; Arzita Arzita (Agritrop : Jurnal Ilmu-Ilmu Pertanian (Journal of Agricultural Science), 2025)
Soybeans (Glycine max (L.) Merril) are an essential food commodity and a source of vegetable protein. Soybean growth and yield can be improved by increasing soil fertility through organic matter. This study aimed to determine the optimal effect of a combination of decanter solids and banana peel POC on soybean growth and yield. This study used a Randomized Block Design (RBD) with nine treatment levels, The study used nine combinations of solid decanter dosages (5, 10, and 15 ton/ha) with POC banana peel fertilizer concentrations (10%, 30%, and 50%), namely: P1 (5 ton/ha + 10%), P2 (5 ton/ha + 30%), P3 (5 ton/ha + 50%); P4 (10 ton/ha + 10%), P5 (10 ton/ha + 30%), P6 (10 ton/ha + 50%); P7 (15 ton/ha + 10%), P8 (15 ton/ha + 30%), and P9 (15 ton/ha + 50%). Data were analyzed using analysis of variance (ANOVA) and followed by a DMRT test at the α=5% level. The application of a combination of a decanter solid and banana peel increased plant height, leaf number, pod number per plant, seed weight per plant, and yield per hectare. The application of 10 ton ha⁻¹ of decanter solid + 10% banana peel POC was the best combination for increasing soybean growth and yield